2019
DOI: 10.3390/molecules24152691
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Nitric Oxide-Responsive Protein in Arabidopsis thaliana

Abstract: In plants, much like in animals, nitric oxide (NO) has been established as an important gaseous signaling molecule. However, contrary to animal systems, NO-sensitive or NO-responsive proteins that bind NO in the form of a sensor or participating in redox reactions have remained elusive. Here, we applied a search term constructed based on conserved and functionally annotated amino acids at the centers of Heme Nitric Oxide/Oxygen (H-NOX) domains in annotated and experimentally-tested gas-binding proteins from lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 78 publications
(100 reference statements)
1
13
0
Order By: Relevance
“…exist in complex proteins with other primary domains and varied architectures (Figure 4B). Mutations to either the "H" or "Y" residues impaired heme binding and concomitantly also the ability to sense NO (Figure 4C) (Zarban et al, 2019;Wong et al, 2020). In general, candidates retrieved from the motif search that display the described structural features, will The domain organizations of ABA-interacting centers identified using a motif-based approach from Arabidopsis thaliana (At), are illustrated as 2-dimensional bars and aligned at their corresponding H-NOX centers.…”
Section: Identification Of Heme-containing Gas Sensors In Complex Promentioning
confidence: 99%
“…exist in complex proteins with other primary domains and varied architectures (Figure 4B). Mutations to either the "H" or "Y" residues impaired heme binding and concomitantly also the ability to sense NO (Figure 4C) (Zarban et al, 2019;Wong et al, 2020). In general, candidates retrieved from the motif search that display the described structural features, will The domain organizations of ABA-interacting centers identified using a motif-based approach from Arabidopsis thaliana (At), are illustrated as 2-dimensional bars and aligned at their corresponding H-NOX centers.…”
Section: Identification Of Heme-containing Gas Sensors In Complex Promentioning
confidence: 99%
“…It therefore remains to be explained how NO positively influences the substrate degradation of the PCO branch of the PRT6 N-degron pathway. NO itself could affect the activities of enzymatic components of the pathway ( Zarban et al , 2019 ) or alter the cellular energy balance in an indirect manner ( Armstrong et al , 2019 ).…”
Section: Nitric Oxide and Hypoxic Stress Crosstalkmentioning
confidence: 99%
“…However, in vitro assessment of the activity of PCOs (Weits et al ; White et al ; White et al ), and analysis of a reconstituted plant PCO‐regulated system for Nt‐Cys degradation in yeast (Puerta et al ) demonstrated that oxidation leading to degradation is possible in the absence of NO ( Saccharomyces cerevisiae has not been shown to produce endogenous NO under standard growth conditions). It, therefore, remains to be discovered how NO exerts a positive influence on degradation of Nt‐Cys substrates in a cellular context, that may include an effect on the activities of enzymic components of the pathway (for example it was recently shown that PRT6 contains a putative NO‐binding domain (Zarban et al )) or indirectly through alterations of cellular energy balance (Greenway and Armstrong ).…”
Section: Enzymatic Components Of Plant N‐degron Pathwaysmentioning
confidence: 99%